Book Notice: . - 1998, Journal of Dharma (Journal of Dharma, 1998)
Roy Eugene Davis Life Surrendered in God. the Kriya-yoga Way of Soul Liberation, Delhi: Motilal Banarsidass, 1995, pp.297, (PB) Rs.195,- Lawrence A. Babb & Susan S. Wadley (eds.), Media and the Transmission of Religion in South Asia, Delhi: Motilal Banarsidass, 1997, pp.viii+298, (PB) Rs.195 Satya prakash, Christianity: A Select Bibliography, Gurgaon, Haryana: Indian Documentation Service, 1986, pp.iv+ 162, Rs.95, Jesu Rajan, Bede Griffiths and Sannyasa, Bangalore: Asian Trading Corporation, 1997 (2nd ed.), pp.xiv+280.